Pertumbuhan Dan Hasil Terong Dengan Aplikasi Pupuk Organik Cair Berbahan Gulma yang Berpotensi Obat - Edi Susilo; Parwito Parwito; Hesti Pujiwati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
Potential yield eggplant crop cultivation can be increased by fertilizing them. Based organic fertilizer liquid organic fertilizer made from medicinal plants is an alternative that should be considered in the future of agriculture. This study aimed to get information that there are certain herbs or a combination of the best as materials for liquid organic fertilizer. Research conducted at the Faculty of Agriculture University of Ratu Samban Bengkulu Utara from November 2016 to February 2017. Research Methods Randomized Design of the single factors with four replications. The treatments are made from medicinal plants liquid organic fertilizer consists Control (G0), liquid organic fertilizer Tithonia diversifolia (G1), Tridax procumben (G2), Ageratum conyzoides (G3), T. diversifolia + T. procumben (G4), T. diversifolia + T. procumben + A. conyzoides (G5),T. procumben + A. conyzoides (G6), and T. diversifolia + A. conyzoides (G7). The results showed that: 1) the treatment of liquid organic fertilizer made from medicinal plants significantly affected the variables plant height, number of pieces, and the eggplant fruit weight. 2) treatment liquid organic fertilizer Tithonia diversifolia + Tridax procumben + Ageratum conyzoides (G5) produced the highest fruit weight when compared to controls. 3) generally made from medicinal weeds liquid organic fertilizer treatment is always generating growth and yield better eggplant.